FORMULASI TABLET HISAP EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) SEBAGAI ANTIOKSIDAN DENGAN VARIASI KONSENTRASI GELATIN SEBAGAI BAHAN PENGIKAT - Ria Cahya Andriana; Mufrod Mufrod; Lutfi Chabib (Universitas Islam Indonesia, 2014)
Peel of mangosteen (Garcinia mangostana L.) contains xanthones especially α-mangostin which have antioxidant activity. The aim on this study was to determine the physical of lozenges extract from mangosteen peel with variation concentration of gelatin 2%, 4%, 6%, 8% and 10%, also to determine the effect formulations of powder into lozenges made with wet granulation method to the percentage reduction of the free radical. The ability of neutralizing free radicals were tested by treating the extract in DPPH with ratio of 3:1. Results showed the tablet hardness were 10.75 kg, 11.13 kg, 11.94 kg, 12.14 kg and 12.35 kg. The friability were 0.84%, 0.73%, 0.71%, 0.60% and 0.50%. Time soluble of the tablet were 7.05 minutes, 9.44 minutes, 9.57 minutes, 11.51 minutes and 13.62 minutes, respectively. Data was analyzed by oneway ANOVA with 95% confidence level. The results showed that all formulas gave better physical properties on granules and tablets produced. Higher concentration of gelatin decreased friability, increased hardness and time-soluble of lozenges. Formula 5 showed the best physical tablet. Percentage reduction of free radicals of extract with DPPH decreased 70.72% after formulated into lozenges.